2015
DOI: 10.1002/bdrb.21135
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intracellular Zinc on Cultures of Rat Cardiac Neural Crest Cells

Abstract: Zn deficiency can result in oxidative stress in cNCC, and subsequent decreases in their population and metabolic activity. These data support the concept that Zn deficiency associated developmental heart defects may arise in part as a consequence of altered cNCC metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…TPEN [K d =2.6×10 −16 M (34)], another Zn chelator, exhibited an increased affinity for Zn 2+ compared with CQ [K d =~1×10 −7 M (34)]. Previous studies (35,36) indicated TPEN was an effective tool for inhibiting Zn in cell models, so it was selected for the in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“…TPEN [K d =2.6×10 −16 M (34)], another Zn chelator, exhibited an increased affinity for Zn 2+ compared with CQ [K d =~1×10 −7 M (34)]. Previous studies (35,36) indicated TPEN was an effective tool for inhibiting Zn in cell models, so it was selected for the in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have illustrated that cardiac malformations induced by Zn deficiency were mainly involved in the great vessels, the outflow tract and the development of the atrium and ventricle, which may possibly due to the anomalous distribution, amount, and function of cardiac neural crest cells (cNCC) during embryonic development ( 55 , 56 ). Indeed, rat cNCC cells cultured in Zn-deficient media exhibited decreased cell viability, and elevated oxidative stress levels and active caspase-3 expressions ( 57 ). Another study used connexin-43 (Cx43) and HNK-1 as biomarkers of cNCC and found abnormal amount and distribution of Cx43 and HNK-1 in the embryonic hearts of Zn-deficient rats ( 56 ).…”
Section: Essential Trace Elements and Congenital Heart Diseasesmentioning
confidence: 99%